2008
DOI: 10.1029/2008gl034592
|View full text |Cite
|
Sign up to set email alerts
|

Investigating error structure of shuttle radar topography mission elevation data product

Abstract: An attempt was made to experimentally assess the instrumental component of error of the C‐band SRTM (SRTM). This was achieved by comparing elevation data of 302 runways from airports all over the world with the shuttle radar topography mission data product (SRTM). It was found that the rms of the instrumental error is about ±1.55 m. Modeling of the remaining SRTM error sources, including terrain relief and pixel size, shows that downsampling from 30 m to 90 m (1 to 3 arc‐sec pixels) worsened SRTM vertical accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…At present, its water level is at 8.0 ± 1.44 m a.s.l. (elevation deduced from the SRTM waterbody dataset with a mean local instrumental error of 1.44 m according to Becek, 2008). Several small streams running down the western slope of the Cordillera de Nahuelbuta are discharging into the lake.…”
Section: Lago Lanalhuementioning
confidence: 99%
“…At present, its water level is at 8.0 ± 1.44 m a.s.l. (elevation deduced from the SRTM waterbody dataset with a mean local instrumental error of 1.44 m according to Becek, 2008). Several small streams running down the western slope of the Cordillera de Nahuelbuta are discharging into the lake.…”
Section: Lago Lanalhuementioning
confidence: 99%
“…A recently obtained SRTM1 dataset (Shuttle Radar Topography Mission; Rabus et al, 2003) is available for the entire Lake Turkana area. This DEM is produced by radar interferometry with 1 arcsec (approximately 30 m) horizontal grid spacing and provides a maximum 5 m absolute vertical error (Becek, 2008;Garcin et al, 2009). In addition, high-resolution (< 1 m) PLEIADES and (5 m) SPOT 5 images were used to focus on selected areas.…”
Section: Methodsmentioning
confidence: 99%
“…All investigations clearly indicated that the vertical accuracy of the SRTM data was significantly higher than required by the SRTM project design. The SRTM-3″ was also investigated using the RWYM [Becek 2008[Becek , 2014. The instrument-induced error of the SRTM-3″ was estimated at 1.55 m [Becek 2008] and 2.2 m [Becek 2014] (1 sigma root-mean-square error [RMSE]).…”
Section: Previous Studies On the Vertical Accuracy Of The Srtmmentioning
confidence: 99%
“…In this paper, we show the results of an investigation into the vertical accuracy of the SRTM-1″ model over the territory of the Republic of Poland using a relatively new method: the runway method (RWYM) [Becek 2008]. The RWYM uses airport runways as elevation reference features for several reasons, including the public domain availability of runway elevation data, their strictly observed technical parameters, their smooth and uniform surfaces and their almost ideally flat (i.e., horizontal) orientation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation